2022
DOI: 10.3233/jad-220536
|View full text |Cite
|
Sign up to set email alerts
|

“I Didn’t Sign Up for This”: Perspectives from Persons Living with Dementia and Care Partners on Challenges, Supports, and Opportunities to Add Geriatric Neuropalliative Care to Dementia Specialty Care

Abstract: Background: In the United States, dementia specialty centers affiliated with centers of excellence for research hold promise as locations to develop innovative, holistic care in care systems otherwise siloed by discipline or payer. Objective: We conducted foundational research to inform development of patient-and family-centered palliative care interventions for dementia specialty centers. Methods: We interviewed persons living with dementia (PLWD), current, and former care partners (CP) recruited from a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Limited research has demonstrated that PWD and CPs receive suboptimal anticipatory guidance related to prognosis and planning. 15,20…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Limited research has demonstrated that PWD and CPs receive suboptimal anticipatory guidance related to prognosis and planning. 15,20…”
Section: Discussionmentioning
confidence: 99%
“…21 A summary of the study in the COREQ framework has been previously published as part of the original study. 15,20…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet the Medicare Hospice Benefit, which provides care to 52% of decedents in the United States in 2019, 2 was not designed for people with dementia (PWD) and their care communities. 3 Common needs among PWD include help managing behavioral symptoms of dementia, pain, breathing problems, disability and falls, and caregiver burden [3][4][5][6] ; these could be insufficiently addressed if hospice processes developed for cancer are followed. Most research on end-of-life care for PWD has focused on hospice recipients who have dementia as principal diagnosis and indication for hospice care.…”
Section: Introductionmentioning
confidence: 99%